Mast cell MrgprB2 in neuroimmune interaction in IgE-mediated airway inflammation and its modulation by β-arrestin2 - Sutradhar, Sangita; Ali, Hydar (Frontiers in Immunology, 2024)
Introduction Allergic asthma has been linked to the activation of mast cells (MCs) by the neuropeptide substance P (SP), but the mechanism underlying this neuroimmune interaction is unknown. Substance P produced from cutaneous nociceptors activates MCs via Mas-related G-protein-coupled receptor B2 (MrgprB2) to enhance type 2 immune response in experimental atopic dermatitis in mice. We recently showed that the adapter protein β-arrestin2 (β-arr2) contributes to MrgprB2-mediated MC chemotaxis. The goals of this study were to determine if MrgprB2 facilitates neuroimmune interaction in IgE (FcεRI)-mediated allergic airway inflammation (AAI) and to assess if this response is modulated by β-arr2. Methods Wild-type (WT), MrgprB2−/− mice and mice with MC-specific deletion of β-arr2 (Cpa3Cre+/β-arr2fl/fl) were passively sensitized with anti-TNP-IgE and challenged with antigen. The generation of SP and MC recruitment in the lung were determined by immunofluorescence and toluidine blue staining, respectively. The transcripts for Tac1, MrgprB2, TNF-α, and Th2 cytokines in lung tissue were assessed by RT-PCR, and the release of selected cytokines in bronchoalveolar lavage (BAL) was determined by ELISA. Eosinophil and neutrophil recruitment in lung tissue and BAL were determined by immunofluorescence staining and flow cytometry, respectively. Goblet cell hyperplasia was determined by periodic acid–Schiff staining. Results Following IgE sensitization and antigen challenge in WT mice, SP generation, and MC recruitment, transcripts for Tac1, MrgprB2, TNF-α, and Th2 cytokine were upregulated when compared to the control challenge. TNF-α, Th2 cytokine production, eosinophil/neutrophil recruitment, and goblet cell hyperplasia were also increased. These responses were significantly reduced in MrgprB2−/− and Cpa3Cre+/β-arr2fl/fl mice. Discussion The data presented herein suggest that SP-mediated MrgprB2 activation contributes to AAI and goblet cell hyperplasia in mice. Furthermore, these responses are modulated by β-arr2, which promotes MC recruitment to facilitate their activation through FcεRI.